1973
DOI: 10.1021/j100626a001
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of atomic oxygen (1D) with methane and ethane

Abstract: Gas-phase reactions of 0(1D) with CH* and with C2He were studied by the photolyses of N2O-CH4 and N2O-C2H6 mixtures using 1849-Á light. Pressure effects and radical scavenging techniques were used to identify the sources of the products. At low pressures, where stabilization of excited alcohol intermediates did not occur, the main path of the Oí1!)) + CH4 reaction was to form CH3 + OH radicals, which ultimately produce C2H6. Molecular elimination giving H2 + CH2O occurred to the extent of 9%, which is the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…The gas-phase kinetics of O(lD) reactions with numerous molecules such as H2, CO, COz, CHI, and various saturated and unsaturated hydrocarbons have been studied in detail, chiefly by CvetanoviC and co-workersl-s and also by DeMore and coworkers. 6 Three major reaction pathways have been proposed2 for the interactions of O(1D) with hydrocarbons in the gas phase, namely, (1) exoergic C-H bond insertion to form a highly energized alcohol intermediate which, depending on its complexity and the bressure a t which the reaction takes place, may be stabilized or decompose by fragmentation to form radical products, (2) H atom abstraction to give direct formation of alkyl and hydroxyl radicals, and (3) elimination of Hz. Recent dynamics studies of O(lD) reactions with CHI have shown that only atomic hydrogen is formed in the gas phase,' suggesting that the observation of molecular hydrogen in earlier gas-and solutionphase work may be due to hydrogen atom abstraction or recombination reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The gas-phase kinetics of O(lD) reactions with numerous molecules such as H2, CO, COz, CHI, and various saturated and unsaturated hydrocarbons have been studied in detail, chiefly by CvetanoviC and co-workersl-s and also by DeMore and coworkers. 6 Three major reaction pathways have been proposed2 for the interactions of O(1D) with hydrocarbons in the gas phase, namely, (1) exoergic C-H bond insertion to form a highly energized alcohol intermediate which, depending on its complexity and the bressure a t which the reaction takes place, may be stabilized or decompose by fragmentation to form radical products, (2) H atom abstraction to give direct formation of alkyl and hydroxyl radicals, and (3) elimination of Hz. Recent dynamics studies of O(lD) reactions with CHI have shown that only atomic hydrogen is formed in the gas phase,' suggesting that the observation of molecular hydrogen in earlier gas-and solutionphase work may be due to hydrogen atom abstraction or recombination reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Three chemical activation studies produced C2H50H in vibrationally excited states and the subsequent decomposition of these provides insight into the decomposition channels of ethanol. The first of these studies involves the insertion of O('D) atoms into a C-H bond of C2H6 to give C2H50H with excess vibrational energy of about 607 kJ/mol, and studies in several laboratories (14,15) found products that could be entirely accounted for by the reactions of free radicals resulting from channels [2] and [5]. Tsang (12) compared these results with theoretical calculations that predicted rate constants for reactions [ I.…”
Section: Introductionmentioning
confidence: 99%
“…= 389.1 f 4.2 kJ. Cvetanovic and coworkers [5] and Lin and DeMore [6] have determined the life times of various vibrationally hot alcohols formed via the insertion of O(l0) into the C-H bond in appropriate hydrocarbons. R R K M calculations [7] will provide a means of relating the thermal and chemical activation results.…”
Section: Introductionmentioning
confidence: 99%